Canagliflozin, dapagliflozin and empagliflozin monotherapy for treating type 2 diabetes: systematic review and economic evaluation - Rhona Johnston; Olalekan Uthman; Ewen Cummins; Christine Clar; Pamela Royle; Jill Colquitt; Bee Kang Tan; Andrew Clegg; Saran Shantikumar; Rachel Court; J Paul O’Hare; David McGrane; et al. (Health Technology Assessment, 2017)
Background: Most people with type 2 diabetes are overweight, so initial treatment is aimed at reducing weight and increasing physical activity. Even modest weight loss can improve control of blood glucose. If drug treatment is necessary, the drug of first choice is metformin. However, some people cannot tolerate metformin, which causes diarrhoea in about 10%, and it cannot be used in people with renal impairment. This review appraises three of the newest class of drugs for monotherapy when metformin cannot be used, the sodium–glucose co-transporter 2 (SGLT2) inhibitors. Objective: To review the clinical effectiveness and cost-effectiveness of dapagliflozin (Farxiga, Bristol-Myers Squibb, Luton, UK), canagliflozin (Invokana, Janssen, High Wycombe, UK) and empagliflozin (Jardiance, Merck & Co., Darmstadt, Germany), in monotherapy in people who cannot take metformin. Sources: MEDLINE (1946 to February 2015) and EMBASE (1974 to February 2015) for randomised controlled trials lasting 24 weeks or more. For adverse events, a wider range of studies was used. Three manufacturers provided submissions. Methods: Systematic review and economic evaluation. A network meta-analysis was carried out involving the three SGLT2 inhibitors and key comparators. Critical appraisal of submissions from three manufacturers. Results: We included three trials of dapagliflozin and two each for canagliflozin and empagliflozin. The trials were of good quality. The canagliflozin and dapagliflozin trials compared them with placebo, but the two empagliflozin trials included active comparators. All three drugs were shown to be effective in improving glycaemic control, promoting weight loss and lowering blood pressure (BP). Limitations: There were no head-to-head trials of the different flozins, and no long-term data on cardiovascular outcomes in this group of patients. Most trials were against placebo. The trials were done in patient groups that were not always comparable, for example in baseline glycated haemoglobin or body mass index. Data on elderly patients were lacking. Conclusions: Dapagliflozin, canagliflozin and empagliflozin are effective in improving glycaemic control, with added benefits of some reductions in BP and weight. Adverse effects are urinary and genital tract infections in a small proportion of users. In monotherapy, the three drugs do not appear cost-effective compared with gliclazide or pioglitazone, but may be competitive against sitagliptin (Januvia, Boehringer Ingelheim, Bracknell, UK). Funding: The National Institute for Health Research Health Technology Assessment programme.